Tripartite motif‐containing 37 (TRIM37) promotes the aggressiveness of non‐small‐cell lung cancer cells by activating the NF‐κB pathway. Issue 3 (4th October 2018) - Li, Yun; Deng, Liwen; Zhao, Xiaohui; Li, Bohan; Ren, Dong; Yu, Lihong; Pan, Hehai; Gong, Qing; Song, Libing; Zhou, Xiang; Dai, Ting
Abstract: Non‐small‐cell lung cancer (NSCLC), in which the NF‐κB pathway is constitutively activated, is one of the most common malignancies. Herein, we identify an E3 ubiquitin ligase, tripartite motif‐containing 37 (TRIM37), participating in the K63 polyubiquitination of TRAF2, which is a significant step in the activation of NF‐κB signaling. Both the mRNA and the protein expression levels of TRIM37 were much higher in NSCLC cell lines and tissues than in normal bronchial epithelial cells and matched adjacent non‐tumor tissues. TRIM37 expression correlated closely with clinical stage and poor survival in NSCLC. Overexpression of TRIM37 antagonized cisplatin‐induced apoptosis, induced angiogenesis and proliferation, and increased the aggressiveness of NSCLC cells in vitro and in vivo, whereas inhibition of TRIM37 led to the opposite effects. Gene set enrichment analysis (GSEA) showed that TRIM37 expression significantly correlated with NF‐κB signaling. Furthermore, we found that TRIM37 bound to TRAF2 and promoted K63‐linked ubiquitination of TRAF2, sustaining the eventual activation of the NF‐κB pathway. Mutation in the ring finger domain of TRIM37, a hallmark of E3 ubiquitin ligases, led to loss of the ability to promote K63 polyubiquitination of TRAF2 and activate NF‐κB signaling. Taken together, our findings provide evidence that TRIM37 plays an important role in constitutive NF‐κB pathway activation and could serve as a prognostic factor and therapeutic target in NSCLC. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.